Structural study of two-dimensional semiconductors using four-dimensional scanning transmission electron microscopy - Wen, Y (2021)
Graphene has shown superior mechanical properties, electronic and thermal conductivity, and room temperature quantum hall effect that enables its wide application in nanoelectronics. Due to its gapless feature, other two-dimensional (2D) materials like transition metal dichalcogenides (TMDs) have drawn attention and have been extensively studied for their application in optoelectronics and photonics. However, the atomic defect structures brought in during synthesis will affect these properties and thus a thorough understanding is needed. 4D-STEM is a characterization method that captures the convergent beam electron diffraction (CBED) pattern to allow post-acquisition reconstruction including orientation and strain mapping, position averaged CBED, and ptychography. This doctoral project focused on using 4D-STEM to characterize graphene, MoS2, and WS2 with atomic defective structures by producing a series of maps of the local electronic environment with atomic resolution.